Rút gọn các biểu thức sau: a) 4x2(5x2 + 3) - 6x (3x2 - 2x + 1) - 5x3(2x - 1);
Câu hỏi:
Rút gọn các biểu thức sau:
a) 4x2(5x2 + 3) - 6x(3x3 - 2x + 1) - 5x3(2x - 1);
b) 32x(x2−23x+2)−53x2(x+65).
Trả lời:
Lời giải:
a) 4x2(5x2 + 3) - 6x(3x3 - 2x + 1) - 5x3(2x - 1)
= 4x2.5x2 + 4x2.3 + (-6x).3x3 + (-6x).(-2x) + (-6x).1 + (-5x3).2x + (-5x3).(-1)
= 20x4 + 12x2 + (-18x4) + 12x2 + (-6x) + (-10x4) + 5x3
= 20x4 + 12x2 - 18x4 + 12x2 - 6x - 10x4 + 5x3
= (20x4 - 18x4 – 10x4) + 5x3 + (12x2 + 12x2) - 6x
= –8x4 + 5x3 + 24x2 - 6x
b) 32x(x2−23x+2)−53x2(x+65)
= 32x.x2 + [32.(−23)]x.x +32x.2 + (−53x2).x +(−53x2).65
= 32x3 - x2 + 3x −53x3 - 2x2
= (32x3−53x3) + (-x2 - 2x2) + 3x
= (96x3−106x3) + (-3x2) + 3x
= -1/6x3 - 3x2 + 3x